2009
DOI: 10.3997/1873-0604.2009012
|View full text |Cite
|
Sign up to set email alerts
|

Preferential fluid flow pathways in embankment dams imaged by self‐potential tomography

Abstract: Special Issue on Hydrogeophysics - Methods and ProcessesInternational audienceWe invert self-potential data in order to locate anomalous water flow pathways in dams and embankments and to estimate the seepage velocity. The inversion of the self-potential data is performed using the modified singular value decomposition for the inverse problem using a linear formulation of the forward problem. The kernel is solved numerically accounting for the topography of the system and the resistivity distribution, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 69 publications
(87 reference statements)
1
65
0
2
Order By: Relevance
“…While self-potential mapping has been applied for a long time to detect preferential fluid flow pathways in embankments and earth dams (Bogoslovsky and Ogilvy 1973;Gex 1980;Merkler et al 1989;Wilt and Corwin 1989;AlSaigh et al 1994;Howie 2001, 2003), it has recently emerged as a powerful quantitative method in determining flow properties in such environments (Rozycki et al 2006;Sheffer and Oldenburg 2007;Rozycki 2009;Bolève et al 2009). The self-potential method was used by Rozycki et al (2006) to diagnose quantitatively leakages in dams and embankments.…”
Section: Applicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…While self-potential mapping has been applied for a long time to detect preferential fluid flow pathways in embankments and earth dams (Bogoslovsky and Ogilvy 1973;Gex 1980;Merkler et al 1989;Wilt and Corwin 1989;AlSaigh et al 1994;Howie 2001, 2003), it has recently emerged as a powerful quantitative method in determining flow properties in such environments (Rozycki et al 2006;Sheffer and Oldenburg 2007;Rozycki 2009;Bolève et al 2009). The self-potential method was used by Rozycki et al (2006) to diagnose quantitatively leakages in dams and embankments.…”
Section: Applicationsmentioning
confidence: 98%
“…Kulessa et al (2003a, b) showed that high self-potential signals are generated during Earth tide deformation of glaciers and groundwater flow in permeable channels organized between the glaciers and the underlying substratum. Bolève et al (2009) developed a scheme to locate leakages in embankments and to determine the flow rate in the leaking area (Fig. 5).…”
Section: Applicationsmentioning
confidence: 99%
“…Despite the complications mentioned above, the SP method continues to receive considerable interest in hydrogeology as SP data are sensitive to contaminant transport (e.g., Maineult et al, 2004Maineult et al, , 2005Revil et al, 2009), redox processes (e.g., Linde and Revil, 2007), flow in saturated (e.g., Maineult et al, 2008;Bolève et al, 2009;Jardani et al, 2007) and unsaturated porous media (e.g., Thony et al, 1997;Doussan et al, 2002;Linde et al, 2007a), flow in fractures (e.g., Wishart et al, 2006), the water table elevation (e.g., Fournier, 1989;Revil et al, 2003;Rizzo et al, 2004), or the thickness of the vadose zone (Aubert and Yéné Atangana, 1996), etc. For example, the SP method might potentially be used to estimate water fluxes in the vadose zone (Thony et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, ERT fails to identify local groundwater flow direction because it is not sensitive to the groundwater fluxes, in contrast to the self-potential (SP) technique (Corwin and Hoover, 1979;Sill, 1983;Fournier, 1989;Aubert and Atangana, 1996). SP data have been used to detect flow paths (Fagerlund and Heinson, 2003;Revil et al, 2005;Jardani et al, 2006;Suski et al, 2008), leakages in dams (Al-Saigh et al, 1994;Bolève et al, 2009), and more recently to infer by inversion the fluxes within the preferential flow path (Jardani et al, 2007;Bolève et al, 2009). The last requires the knowledge of the streaming potential coupling coefficient (Revil et al, 1999) and supposes that the electrokinetic effect is the dominant contribution of the SP signals.…”
Section: Introductionmentioning
confidence: 99%